Blue rubber bleb nevus syndrome: our experience and new endoscopic management. Issue 33 (August 2017) - Chen, Wenguo; Chen, Hongtan; Shan, Guodong; Yang, Ming; Hu, Fengling; Li, Qi; Chen, Lihua; Xu, Guoqiang
Abstract : Abstract: The aim of our study is to enhance the awareness of blue rubber bleb nevus syndrome (BRBNS) through the patients in our hospital and introduced a new measure of endoscopic intervention. A retrospective review of 5 patients, who were diagnosed as BRBNS in our hospital from January 2013 to January 2017, was conducted. Data were collected with regard to demographics, clinical presentation, endoscopic and imaging findings, management, and follow-up data. In total of 5 patients, the mean age was 28.8 years, range 16 to 44 years (male/female, 1/4) with the average initial age of onset 15.4 years. No family history was identified in our group. Physical examination showed multiple cutaneous lesions in 2 patients (40%, 2/5). All the 5 patients had gastrointestinal tract vascular malformations; stomach involved in 2 cases, large intestine in 2 cases, and small intestine involved in 3 cases. Lesions in the visceral organs and tissue were found in 1 patient. Gastrointestinal bleeding was its main symptom (3/5, 60%). Laboratory investigations revealed anemia in 4 patients and abnormality of coagulopathy in 2 patients with severe anemia. Conservative approach was recommended in 3 cases that included iron supplementation, drug hemostasis, and/or blood transfusion. An innovatively therapeutic approach with endoscopic submucosal dissection (ESD) procedure was used successfully in 1 patient with 2 polypoid BRBNS lesions in rectum. BRBNS is a very rare vascular malformation syndrome with unclear etiopathogenesis and noncurative treatments. ESD procedure was a feasible approach to remove the partial gastrointestinal lesions.